The 2016 revised ACR criteria for diagnosis of giant cell arteritis – Our case series: Can this avoid unnecessary temporal artery biopsies?. (2017) - Sait, Mohamed R.; Lepore, Mario; Kwasnicki, Richard; Allington, Jonathan; Balasubramanian, Rajesh; Somasundaram, Santosh K.; Vashisht, Rajiv; Barkeji, Musa
Abstract: Background: Temporal artery biopsy (TAB) is considered the gold standard for diagnosing Giant Cell Arteritis (GCA). The aim of this study was to compare the functional utility of the 2016 revised ACR (rACR) criteria against the original ACR criteria with a view to avoiding TABs in select groups. We also aimed to investigate the temporal relationship of positive biopsies. Methods: A retrospective study was conducted of patients undergoing TAB from August 2014 to August 2016, at a DGH. Data collected included patient demographics, history, biochemistry, time to TAB from commencement of steroids and histology. The ACR and the rACR scores and the relative TAB results were analysed using ROC to determine statistical measures of performance. Different score thresholds were applied to propose a clinical tool to be used as an adjunct in the management of suspected GCA. Results and Discussion: Forty two TABs were performed during this period of which 10 were males and 32 females. ROC analysis showed significant relationships between both ACR and rACR to TAB result. The AUC for rACR was 0.880 (p < 0.001) and for ACR was 0.737 (p = 0.023). The median time to TAB from referral was 10 days (IQR 6–13). The diagnostic yield was highest within 8 days (41%) of all positive biopsies. Conclusion: This study demonstrates the potential value of the rACR criteria and a simple clinical tool is proposed to stratify relevant patients with a view to avoiding unnecessary TAB. Prolonged wait between referral to TAB is also likely to reduce its validity. Highlights: Risk stratification of the 2016 revised ACR (rACR) criteria is a simple clinical tool proposed for the diagnosis of GCA. This could help avoid unnecessary Temporal artery biopsies in select group of patients. Temporal artery biopsies should be performed early on from commencement of steroids.